The effects of aeroelasticity on aircraft stability and control [microfilm] - Neoh, Chee Uee (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 2002